Regulating the automobile - Crandall, Robert W.; Gruenspecht, Howard K.; Keeler, Theodore E.; Lave, Lester B. (Washington, D.C. : Brookings Institution, 1986)
This publication provides an empirical assessment of the costs and benefit of all three programs on automobile regulation imposed by the government and analyzes their combined effects and the conflicts among them.
Includes bibliographical references and index.
gp 23/01/2019
Loans
Keywords: Automobiles